Analisis Sifat Mekanik Pada Material Standar Paduan COR ALSi10Mg(b) Dari Skrap Aluminium - Yuli Nurasri; Budi Santoso; Mulianti Mulianti; Titiek Deasy Saptaryani (Jurnal Teknik Mesin, 2023)
The metal industry in Tegal Regency is classified into ferrous and non-ferrous metal industries. The shipping component industry is the leading producer of the non-ferrous metal industry. The problem faced by the non-ferrous metal processing industry, especially the Small and Medium Industry ship components is the availability of standard materials as raw materials at affordable prices. Instead, SMEs use scrap material to reduce selling prices, as a result of which product quality does not meet the required specifications. This research made 2 (two) formulas of AlSi10Mg(b) from an aluminum scrap mixture where AlSi10Mg(b) is one of the standard materials of cast aluminum alloy recognized by Biro Klasifikasi Indonesia (BKI). The study aimed to recommend raw material formulas to SMEs to ship components to make products according to BKI standards. The research began by collecting a database of aluminum scrap composition, then simulating calculations with an Excel program to obtain theoretical chemical composition so that the need for aluminum scrap was produced. The two standard material formulas of AlSi10Mg(b) are made from different main scrap where formula 1 is the piston, and formula 2 is the brake lining with the supporting scrap is the pan, aluminum elbow, and aluminum plate as well as the AlSi49 and AlMg20 master alloys. The simulation results are then cast with the sand-casting method. The cast results are made of specimens testing chemical composition and hardness. The results of the chemical composition test show that both formulas are in accordance with the conditions of AlSi10Mg(b) cast alloy, namely the percentage of Silicon (Si) and Magnesium (Mg) in formula 1 is 9.16% and 0.39% while formula 2 is 10.69% and 0.22%. Both formulas are still with Copper (Cu) content that still exceeds the limit of above 0.1%. The hardness value has met BKI standards above 50HBN.